Analisa Penerapan Keselamatan Dan Kesehatan Kerja pada Pekerjaan Pigging di Pertamina Hulu Rokan - Muthia Anggraini; Irwan Nazif; Fadrizal Lubis (Universitas Teuku Umar, 2022)
PT Pertamina Hulu Rokan routinely performs pigging work. In one of the segments at PT. Pertamina Hulu Rokan 30” CGS 5 – Dumai oil pipeline with a pipe length of 45,500 meters is one of the segments that pigging activities routinely carry out. Based on the phenomena that occur in pigging activities, there are safety risks from physical hazards to the operator, especially from gas pressure in the pipe both during preparation for receiving pigs and taking pigs. The purpose of this study was to find out how the implementation of Occupational Safety and Health in Pigging Work at Pertamina Hulu Rokan based on PP No. 50 of 2012. This research method is in the form of collecting data from interviews with 10 respondents related to work from the lowest level to the supervisor level and collecting data related to job cost analysis. The results of this study are the application of the Occupational Health and Safety Management System (SMK3) on pigging work at 30” CGS 5 - Dumai reaching a value of 95.31% belonging to category number 3, namely the level of control of the implementation of 85-100% including a satisfactory level, as the initial category with the fulfillment of 61 criteria out of a total of 64 criteria and there are 3 criteria that are not met with a value of 4.69% less category. The conclusion of this research is the application of SMK3 in Pertamina Hulu Rokan based on PP no. 52 of 2012 is considered satisfactory